Metatranscriptomic holobiont analysis of carbohydrate-active enzymes in the millipede Telodeinopus aoutii (Diplopoda, Spirostreptida) - Sardar, Puspendu; Šustr, Vladimír; Chroňáková, Alica; Lorenc, František (Frontiers in Ecology and Evolution, 2022)
Millipedes, as key decomposers of soil organic matter, contribute to lignocellulose degradation and nutrient cycling. Lignocellulose (cellulose, lignin and hemicellulose) is the main component of leaf litter, and its digestion requires the action of multiple carbohydrate-active enzymes (CAZymes). In most invertebrates, the degradation of lignocellulose depends on its association with microbial enzymes. To test their importance in millipedes, we analysed metatranscriptomic data from the tropical millipede T. aoutii as the first study on a Myriapoda holobiont. Functional annotation included identification of expressed genes coding CAZymes in the host and its intestinal microbiota, in the foregut, midgut and hindgut, compared to non-intestinal tissues. Metatranscriptomic data were complemented with the enzyme activity measurement in intestinal homogenates of the same species. The midgut of T. aoutii exhibited the greatest diversity of expressed endogenous CAZymes. Direct activity measurements and analysis of expressed genes revealed the high potential of endogenous amylolytic activity in the midgut. In the intestine of T. aoutii, only traces of cellulolytic activity were detected by direct measurements and the expression of endogenous cellulases was not confirmed, with the exception of family AA15, known to contain a putative lytic cellulose monooxygenase. The negligible ligninolytic and pectinolytic activities in the midgut may be compensated by soil microorganisms that predigest plant litter. Microbial degradation of lignocellulose in the millipede is driven by bacteria primarily in the hindgut, although some of bacterial cellulases and hemicellulases expressed in the midgut can contribute to the digestive process. The contribution of the intestinal eukaryotic microbiota to CAZymes production was negligible. Expression of amylolytic or chitinolytic enzymes in nematodes and ciliates, supported their commensal feeding on the hindgut bacteria. The low expression levels of fungal CAZymes reflected oxygen-limiting condition in most of intestine volume. The hotspot of the cellulose and hemicellulose degradation represents the hindgut. The importance of the lignocellulose digestion to the millipede nutrition depends on the animals´ ability to absorb the products of hindgut microbial processes through the hindgut epithelium. The activity of the hindgut microbiota may be important for ecological role of millipede holobiont, regarding to the high production of excrements crucial for soil formation.